In situ synthesis of copper nanoparticles on dielectric barrier discharge plasma-treated polyester fabrics at different reaction pHs - Mehravani, Behnaz (2022)
Polyester (PET) fabrics are widely applied in functional textiles due to their outstanding properties such as high strength, dimensional stability, high melting point, low cost, recyclability, and flexibility. Nevertheless, the lack of polar groups in the PET structure makes its coloration and functionalization difficult. The present work reports the one-step in situ synthesis of copper nanoparticles (CuNPs) onto the PET fabric employing sodium hypophosphate and ascorbic acid as reducing and stabilizing agents, at acidic (pH 2) and alkaline pH (pH 11). This synthesis (i) used safer reagents when compared with traditional chemicals for CuNP production, (ii) was performed at a moderate temperature (85 °C), and (iii) used no protective inert gas. The dielectric barrier discharge (DBD) plasma was used as an environmentally friendly method for the surface functionalization of PET to enhance the adhesion of CuNPs. The size of the CuNPs in an alkaline reaction (76–156 nm for not treated and 93.4–123 nm for DBD plasma-treated samples) was found to be smaller than their size in acidic media (118–310 nm for not treated and 249–500 nm for DBD plasma-treated samples), where the DBD plasma treatment promoted some agglomeration. In acidic medium, metallic copper was obtained, and a reddish color became noticeable in the textile. In alkaline medium, copper(I) oxide (Cu2O) was detected, and the PET samples exhibited a yellow color. The PET samples with CuNPs presented improved ultraviolet protection factor values. Finally, a minimal concentration of copper salt was studied to obtain the optimized antibacterial effect against Staphylococcus aureus and Escherichia coli. The functionalized samples showed strong antibacterial efficacy using low-concentration solutions in the in situ synthesis (2.0 mM of copper salt) and even after five washing cycles. The DBD plasma treatment improved the antibacterial action of the samples prepared in the alkaline medium.